Influence of Soil Variation on Diosgenin Content Profile in Costus speciosus from Indo‐Gangetic Plains. Issue 6 (27th April 2021) - Rawat, Poonam; Kumar, Manish; Srivastava, Akanksha; Kumar, Bhanu; Misra, Ankita; Pratap Singh, Satyendra; Srivastava, Sharad
Abstract: Costus speciosus is a rich source of commercially important compound Diosgenin, distributed in different regions of India. The present investigation was aimed to quantify diosgenin through High Performance Thin Layer Chromatography in 34 germplasms of Costus speciosus and also to identify the superior sources and to correlate the macronutrients of rhizospheric soil. The starch content varied in microscopic examination and correlated inversely (r=−0.266) with diosgenin content. Findings revealed that the extraction process with acid hydrolysis yielded higher diosgenin content (0.15–1.88 %) as compared to non‐hydrolysis (0.009–0.368 %) procedure. Germplasms from Uttar Pradesh (NBCS‐4), Jharkhand (NBCS‐39) and Bihar (NBCS‐2) were identified as elite chemotypes based on hierarchical clustering analysis. The phosphorous content of respective rhizospheric soil correlated positively (r=0.742) with diosgenin content. Findings of present study are useful to identify the new agrotechniques. The elite germplasms can also be used as quality planting material for large scale cultivation in order to assure a sustained supply to the herbal drug industry. Abstract :